Distribution and Habitat Status of Ganges River Dolphin (Platanista gangetica) in Mohana River Segment of Western Nepal - Khatiwada, Sunil; Chalise, Mukesh K.; Sharma, Shailendra (Journal of Institute of Science and Technology, 2019)
An endangered species of Ganges River dolphin (Platanista gangetica) in Mohana River and its population status was reported employing synchronized point count. The physicochemical parameters of water were determined using pseudo-random water sampling along various segments of the river. Mean sighting rate during monsoon, 2018 and pre-monsoon, 2016 were one dolphin per 1.355 km and 1.65 km, respectively, with a clumped distribution. Physico-chemical parameters test showed that Mohana River was slightly alkaline with high turbidity and low vulnerability to an acid deposition with a high amount of total phosphorous, indicating a high eutrophication productivity range for both seasons. Water quality is not significantly different during the study period, and the aquatic parameter showed that agricultural activities along the river may have an influence on water quality.